THE EFFECT OF DIFFERENT PACKAGING ON THE QUALITY OF REBON SHRIMP (Acetes erythraeus) PASTE DURING ROOM TEMPERATURE STORAGE By: - Sari, Puspita; Dahlia, Dahlia; Desmelati, Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT This study aims to determine the effect of different packaging on the quality of shrimp (Acetes erythraeus) paste during room temperature storage. The method used was an experimental method, namely a non-factorial randomized block design (RBD) with the treatment of HDPE plastic, glass bottles (BK) and aluminum foil (AF). The quality parameters tested in this study were organoleptic tests (appearance, aroma, taste and texture), and proximate tests (moisture content, ash content, protein content and fat content). The results showed that the rebon shrimp paste with different types of packaging during room temperature storage showed that aluminum foil (AF) packaging was the best treatment with organoleptic value, appearance 5.50, aroma 7.76, taste 6.14, texture 7.28 and had a moisture content value of 33.37%, ash 0.01%, protein content of 9.57% and fat content of 0.33%. Keywords: Petis, rebon shrimp, type of packaging, storage time